Measuring the Impact of Apply Reverse Engineering Approach to Production Cost Reduction on The Economic Growth - Al Uwaimri, Ahmed (Yayasan Riset dan Pengembangan Intelektual, 2025)
The quantitative results from the application of the reverse engineering approach showed a reduction in extraction costs by 1.8, compared to the target reduction of 3.8. Meanwhile, the total cost per oil barrel increased to 27, exceeding the target cost of 25.2 per barrel. Oil production in the Sultanate of Oman increased by 3.6%, reaching 3,323,800 barrels by the end of January 2023. The average oil price in 2022 was 94 per barrel. Based on these figures, the profit margin after achieving the target cost reduction is 94 – 25.2 = 68.8, resulting in a total profit of 3,323,800 × 68.8 = 228,677,440. The reverse engineering approach in reducing production costs helps increase profit margins and supports oil-based economies in generating higher revenues, thereby contributing to the promotion of economic growth in oil-exporting countries. As an innovative tool, the application of reverse engineering in production cost reduction demonstrates a significant impact on promoting economic growth in oil-exporting economies.